2023
DOI: 10.3389/fpls.2023.1123436
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory network of GSK3-like kinases and their role in plant stress response

Abstract: Glycogen synthase kinase 3 (GSK3) family members are evolutionally conserved Ser/Thr protein kinases in mammals and plants. In plants, the GSK3s function as signaling hubs to integrate the perception and transduction of diverse signals required for plant development. Despite their role in the regulation of plant growth and development, emerging research has shed light on their multilayer function in plant stress responses. Here we review recent advances in the regulatory network of GSK3s and the involvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 129 publications
1
5
0
Order By: Relevance
“…Glycogen synthetase kinase GSK3, also known as hairy kinase (SK), is a versatile kinase that was originally discovered in rabbits [45]. In plants, BR-INSENSITIVE 2 (BIN2/SK21) is the best-known representative of GSK3 [29]. Our present research revealed that transgenic Arabidopsis lines that expressed HbBIN2 experienced far more severe cold stress damage than wild-type varieties (Figure 4).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Glycogen synthetase kinase GSK3, also known as hairy kinase (SK), is a versatile kinase that was originally discovered in rabbits [45]. In plants, BR-INSENSITIVE 2 (BIN2/SK21) is the best-known representative of GSK3 [29]. Our present research revealed that transgenic Arabidopsis lines that expressed HbBIN2 experienced far more severe cold stress damage than wild-type varieties (Figure 4).…”
Section: Discussionmentioning
confidence: 61%
“…Unlike humans, which have only two GSK3 isoforms, plants have evolved multiple GSK3 homologs [29,51]. Oryza sativa and Arabidopsis have 9 and 10 GSK3-like kinases, respectively [29,52].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations